Korzyści oferowane odbiorcom w programach kształtujących proekologiczny styl życia - Zaremba-Warnke, Sabina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article contains the main target group of Ecological Life Style Projects, characteristics of Ecological Life Style, and analyses benefits offered by Ecological Life Style Projects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 120-128